Pengembangan E-Modul Projek Penguatan Profil Pelajar Pancasila (P5) Berbasis Project Based Learning (PjBL) untuk Meningkatkan Minat Belajar dan Kemampuan Berpikir Kritis Peserta Didik di SMA Negeri 1 Wori: Penelitian - Maharani Angelika Elshadai Rori; Revolson A. Mege; Femmy R. Kawuwung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The implementation of the independent curriculum emphasizes character building through the Pancasila Student Profile Strengthening Project (P5) to produce students who are critical, creative, and collaborative. The implementation of P5 at SMA Negeri 1 Wori does not yet have project-based learning guides that support students' interests and critical thinking skills in biology learning. Factors such as the learning environment and motivation influence critical thinking skills, in that motivation plays a role in increasing learning interest. To address this, this study aims to design a P5 e-module based on Project-Based Learning (PjBL) as an interactive learning medium. The research uses a Research and Development (R&D) approach with the ADDIE model, through the following stages: Analyze, Design, Development, Implementation, and Evaluation. Data was collected through observation, interviews, questionnaires, and pre- and post-tests. The e-module was developed through validity assessment by media experts, subject matter experts, and question experts. The validity of the e-module was rated at 87.1% by media experts, 98.5% by subject matter experts, and 100% by question experts. A pilot study with Grade XII students showed an increase in learning interest of 29.75% and critical thinking skills of 32.2%.